2018
DOI: 10.1111/codi.14337
|View full text |Cite
|
Sign up to set email alerts
|

Transanal endoscopic microsurgery as day surgery – a single‐centre experience with 500 patients

Abstract: Outpatient TEM is safe and carries a low risk of readmission. In centres with an outpatient TEM strategy, predictors of hospital admission include proximal tumours, prolonged surgical time and open management of the surgical defect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 21 publications
(33 reference statements)
0
3
0
Order By: Relevance
“…Infection rates correspond to reported rates in the literature between 1% and 10%. 18,23 However, there were variations in patient selection and protocols across the included studies. Bowel preparation and prophylactic antibiotics were given in the randomised controlled trial.…”
Section: Discussionmentioning
confidence: 99%
“…Infection rates correspond to reported rates in the literature between 1% and 10%. 18,23 However, there were variations in patient selection and protocols across the included studies. Bowel preparation and prophylactic antibiotics were given in the randomised controlled trial.…”
Section: Discussionmentioning
confidence: 99%
“…The early inclusion of 2-surgeon collaboration on the novel perineal approach, combined with extensive experience with transanal endoscopic microsurgery before TaTME introduction, was important in avoiding these potentially severe complications. 24 Consistent with expert guidelines introduced in Canada and the United States, careful patient selection and formal proctored training are crucial. 5,6 As reported by Robertson et al, 25 TaTME comprised a select proportion of patients with its uptake at our institution.…”
Section: Discussionmentioning
confidence: 99%
“…For "difficult", endoscopically unresectable rectal polyps, transanal excision is the method of choice. It has been shown that transanal endoscopic microsurgery and transanal minimally invasive surgery are effective techniques for the surgical removal of these polyps [46,47].…”
Section: Endoscopic Mucosal Resectionmentioning
confidence: 99%